Theological and Cultural Construction: Resilience Strategies of the To Sallang Minority in A Multicultural Society - Ilham, M.; Hasyim, Baso; Langaji, Abbas; Hasanuddin, Irfan; Barsihannor, Barsihannor (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2023)
To Sallang is a term addressed to minority Muslims who live in Toraja. Even though they are a minority, they can live side by side, without losing their Islamic identity. This research aims to find out To Sallang's resilience strategy to survive among the mainstream religions and customs of the Toraja people who are predominantly Christian. In addition, it also aims to explore religious aspects that can strengthen To Sallang community to survive and adapt to a multicultural society. Data were collected through observation, in-depth interviews, and documentation. The research results show that To Sallang manages to maintain their social identity as a native of Toraja descent, as well as negotiate personal identity as a Muslim community by adapting their genius and creative assimilation to universal religious values and local wisdom (indigenous knowledge). Through theological concepts such as fitrah-sunnatullah (natural law), hablum min al-nas (social interaction), hurmatu al-takrim (respect and honor), and al-ma'ruf (values of goodness and wisdom that are rooted in the traditions of society) synchronized with local wisdom values such as sikamali (love-miss each other), siangga' (mutual respect), and siangkaran (help each other), To Sallang can present a comprehensive picture of religiosity that accommodates religious aspirations with cultural characteristics. To Sallang strategy could be the best practice and reference to build religious and cultural co-existence since they can survive with their Islamic identity and local wisdom to live together in a multicultural society. It can also be a blueprint for religious and cultural harmony in overcoming potential conflicts caused by ethnic and religious differences.